Constructive development of the Leiden house in the 13th and 14th centuries - Orsel, Edwin (Rozwój konstrukcji domów w Lejdzie w XIII i XIV w., 2022)
Leiden is one of the largest medieval cities in the Netherlands. Because the city has never suffered major devastation, for example caused by city fires or wars, there is a rich layered historic city centre. This article discusses the constructive development of Leiden houses in the 13th and 14th centuries and its influences. In recent years, building archaeological research has uncovered the remains of approximately 150 buildings from before or about 1400. Based on this, and in combination with archaeological data, the constructive development of the Leiden house in the 13th and 14th centuries can be outlined. Based on dendrochronologically dated examples, the origin of a typical timber-frame house with brick façades can be established, a confluence of older timber- and stone-building traditions. It is a building type that remains the popular building type in Leiden and far beyond until about 1600. This development is related to the urbanization of Leiden in the 13th century with urban densification, population growth and the emergence of guilds. The issuing of fire prevention measures by the city council and the payment of subsidies also play an important role. The development is also determined by the availability of building materials. According to dendrochronological data, construction timber has to be imported from afar, from Westphalia or Emsland (Germany). Natural stone was not available locally and had to be supplied from far away regions in Germany or Belgium, until a flourishing brick industry developed along the Rhine in the 13th century, immediately outside the city gates of Leiden. By inventively combining brick walls and a wooden supporting structure by specialized carpenters, high-quality and fire-safe houses were created, responding to the demands of the growing citizenry and the city authorities in a nascent city.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 17-25
Keywords: architektura; Lejda; archeologia budowli; historia budownictwa; domy średniowieczne; Leiden; building archaeology; construction history; medieval houses